(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to evaluate the construction faults associated with complete dentures made by clinical students. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at Prosthodontics; Department Institute of Dentistry; Liaquat University of Medical and Health Sciences Jamshoro from May 2015 to October 2015 Materials and Methods: Total 197 complete denture wearer’s patients were recruited in this study. Faults associated with vertical dimension, centric relation, denture base thickness, finishing and polishing were examined and noted in proforma. Data was analyzed by SPSS version 17.0. Results: Out of 197 patients male and female patients were 56.3% and 43.7% respectively. Vertical dimension was found to be high in 82% patients and centric relation was noted 81% as right and 19% as wrong. According to thickness of denture base plate, 80% were thick and 5% were thin denture base. According to finishing and polishing of dentures, 55% dentures were seen with satisfactory results. Conclusion: It is concluded that the most common faults in construction of complete dentures were high vertical dimension, thick denture base plates and finishing & polishing.